Raw seismic refraction data during cruise RV SONNE SO258/2 (INGON), Indian Ocean off Sri Lanka, profile AWI-20170300 ... - Weigelt, Estella; Geissler, Wolfram H; Altenbernd-Lang, Tabea; Jokat, Wilfried; Werner, Reinhard (PANGAEA, 2025)
As part of the research project INGON (a collaboration between the Alfred Wegener Institute and the GEOMAR), two offshore seismic refraction profiles were obtained during Sonne cruise SO258 to study the separation of India and Antarctica. The acquired data set covers data of 30 stations recorded with three different types of Ocean Bottom Seismometer (OBS)-systems: 12 LOBSTER and 2 NAMMU systems of the AWI belonging to the DEPAS pool (German Instrument Pool for Amphibian Seismology) and 20 OBS systems of GEOMAR. The raw-data acquired with AWI-OBS were recorded with 6d6-recorders, manufactured by KUM in Kiel, Germany. The AWI-OBS were equipped with a Seismometer (3 channels) and a hydrophone (1 channel). The raw-data of the AWI-OBS is in 6d6-format and can be converted with software from SEND and KUM to segy. The raw-data acquired with GEOMAR-OBS were recorded with Sercel-recorders or Geolog-recorders. The GEOMAR-OBS were equipped with a geophone instead of a seismometer (3 channels) and a hydrophone (1 ...